Relational Contracts and the Economic Well-Being of Nations - Bohdan Kukharskyy; Michael Pflüger (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2011)
Informal long-term relationships and mutual confidence play a crucial role in modern economies in at least two dimensions. First, the performance of firms is strongly affected by their capacity to solve organizational questions effectively and this capacity is apparently strongly related to their ability to maintain informal long-term relationships. Second, countries that are better at maintaining unwritten agreements and where interactions are more strongly guided by a sense of trust fare better in terms of economic welfare than others. This paper provides a simple general equilibrium model which reconciles these two findings: we offer a micro-founded explanation of how the trust that prevails in an economy gets transmitted into higher economic well-being and we thereby highlight the role of managers with low time preference. Our analysis builds on the model of Antràs and Helpman (2004) and a formalization of the notion of relational contracting developed in Baker, Gibbons and Murphy (2002).
Keywords: D23; F14; L14; L22; 330; aggregate welfare; theory of the firm; relational contracting; firm heterogeneity; Außenwirtschaft; Produktdifferenzierung; Outsourcing; Lieferanten-Kunden-Beziehung; Produktivität; Verhandlungstheorie; Unvollständiger Vertrag; Soziale Wohlfahrtsfunktion; Theorie